Discovery of an Unconventional Centromere in Budding Yeast Redefines Evolution of Point Centromeres - Kobayashi, Norihiko (Curr Biol, 2015)
Centromeres are the chromosomal regions promoting kinetochore assembly for chromosome segregation. In many eukaryotes, the centromere consists of up to mega base pairs of DNA. On such “regional centromeres,” kinetochore assembly is mainly defined by epigenetic regulation [1]. By contrast, a clade of budding yeasts (Saccharomycetaceae) has a “point centromere” of 120–200 base pairs of DNA, on which kinetochore assembly is defined by the consensus DNA sequence [2, 3]. During evolution, budding yeasts acquired point centromeres, which replaced ancestral, regional centromeres [4]. All known point centromeres among different yeast species share common consensus DNA elements (CDEs) [5, 6], implying that they evolved only once and stayed essentially unchanged throughout evolution. Here, we identify a yeast centromere that challenges this view: that of the budding yeast Naumovozyma castellii is the first unconventional point centromere with unique CDEs. The N. castellii centromere CDEs are essential for centromere function but have different DNA sequences from CDEs in other point centromeres. Gene order analyses around N. castellii centromeres indicate their unique, and separate, evolutionary origin. Nevertheless, they are still bound by the ortholog of the CBF3 complex, which recognizes CDEs in other point centromeres. The new type of point centromere originated prior to the divergence between N. castellii and its close relative Naumovozyma dairenensis and disseminated to all N. castellii chromosomes through extensive genome rearrangement. Thus, contrary to the conventional view, point centromeres can undergo rapid evolutionary changes. These findings give new insights into the evolution of point centromeres.